Distinct Bimodal Roles of Aromatic Molecules in Controlling Gold Nanorod Growth for Biosensing. (26th June 2017) - Soh, Jun Hui; Lin, Yiyang; Thomas, Michael R.; Todorova, Nevena; Kallepitis, Charalambos; Yarovsky, Irene; Ying, Jackie Y.; Stevens, Molly M.
Abstract : New aromatic molecule–seed particle interactions are examined and exploited to control and guide seed‐mediated gold nanorod (Au NR) growth. This new approach enables better understanding of how small molecules impact the synthesis of metallic nanostructures, catalyzing their use in various biomedical applications, such as plasmonic biosensing. Experimental studies and theoretical molecular simulations using a library of aromatic molecules, making use of the chemical versatility of the molecules with varied spatial arrangements of electron‐donating/withdrawing groups, charge, and Au‐binding propensity, are performed. Au NR growth is regulated by two principal mechanisms, producing either a red or blue shift in the longitudinal localized surface plasmon resonance (LLSPR) peaks. Aromatic molecules with high redox potentials produce an increase in NR aspect ratio and red shift of LLSPR peaks. In contrast, molecules that strongly bind gold surfaces result in blue shifts, demonstrating a strong correlation between their binding energy and blue shifts produced. Through enzymatic conversion of selected molecules, 4‐aminophenylphosphate to 4‐aminophenol, opposing growth mechanisms at opposite extremes of target concentration are obtained, and a chemical pathway for performing plasmonic enzyme‐linked immunosorbent assays is established. This unlocks new strategies for tailoring substrate design and enzymatic mechanisms for controlling plasmonic response to target molecules in biosensing applications. Abstract : Aromatic molecule–seed particle interactions are introduced as a novel chemical approach to control anisotropic growth of gold nanorods (Au NRs). The interaction of seeds with reducing aromatic molecules produces Au NRs with higher aspect ratios and red‐shifted plasmonic peaks, while the interaction with gold surface‐binding molecules yields Au NRs with lower aspect ratios and blue‐shifted peaks. These observations enable more sophisticated engineering of anisotropic nanoparticle growth.